2017
DOI: 10.1080/01443615.2017.1322046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quince with vitamin B6 for treatment of nausea and vomiting in pregnancy: a randomised clinical trial

Abstract: This trial was performed to compare quince (Cydonia oblonga) fruit with vitamin B6 on 76 pregnant women with a gestational age of 6-14 weeks and mild-to-moderate nausea and vomiting (NVP) (40 in the quince and 36 in the B6 group). The 'Pregnancy-Unique Quantification of Emesis' (PUQE-24) scale was used to examine the severity of NVP. The quince syrup (1 tablespoon/TDS) or vitamin B6 tablets (20 mg/TDS) were used as intervention for 1 week. The mean (±SD) age was 27.5 (±5.2) years. The score of the PUQE was dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 17 publications
1
15
0
9
Order By: Relevance
“…Sample size ranged from 27 to 500 women in interventional studies, 187 to 860,215 women in observational studies, and one to five women in case reports. Seven studies collected data during the first trimester of pregnancy; 71,82,85,88,96,105,107 10 during the second trimester; 41,58,67,81,83,84,87,89,101,108 12 during the third trimester; 38,62,64,80,91,92,100,102,103,106,109,110 five throughout pregnancy; 69,70,75,90,95 five around the time of labor (a few hours before or after delivery); 37,59–61,77 nine throughout pregnancy and the postnatal period; 14,31,39,7274,78,79,111 three during the third trimester and the postnatal period; 40,112,113 20 during the postnatal period only; 24,34,56,63,65,66,68,76,86,94,9799,104,114119 and two did not specify the precise point during pregnancy of data collection. 57,93…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sample size ranged from 27 to 500 women in interventional studies, 187 to 860,215 women in observational studies, and one to five women in case reports. Seven studies collected data during the first trimester of pregnancy; 71,82,85,88,96,105,107 10 during the second trimester; 41,58,67,81,83,84,87,89,101,108 12 during the third trimester; 38,62,64,80,91,92,100,102,103,106,109,110 five throughout pregnancy; 69,70,75,90,95 five around the time of labor (a few hours before or after delivery); 37,59–61,77 nine throughout pregnancy and the postnatal period; 14,31,39,7274,78,79,111 three during the third trimester and the postnatal period; 40,112,113 20 during the postnatal period only; 24,34,56,63,65,66,68,76,86,94,9799,104,114119 and two did not specify the precise point during pregnancy of data collection. 57,93…”
Section: Resultsmentioning
confidence: 99%
“…The methods used to identify adverse events and herb–drug interactions were clinical examination; 3741,56,57,59,60,63,70,81,82,105,107112,114119 patient interviews; 61,65,78,86,93,100,106 patient questionnaires; 24,31,34,7274,76,85,90,94,95,9799 diary cards; 62,66,68 laboratory or imaging studies (ie, hematologic and biochemical results, ultrasonography); 71,79,102,120 and review of medical records. 14,64,65,75,77,88,91,92,96,100,113 Eleven studies did not mention how adverse events or herb–drug interactions were identified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations